Population abundance of rhinoceros beetle (Oryctes rhinoceros) at nursery and immature oil palm area / Nurul Fatihah Daud - Daud, Nurul Fatihah (Faculty of Plantation and Agrotechnology, 2019)
Rhinoceros beetle that also known as Oryctes rhinoceros have become incessant dilemma faced by growers in Malaysia. It can cause severe damage to the oil palm (Elaeis guineensis) plantation and its productivity. This study was conducted purposely to compare the population of Rhinoceros beetle in the nursery stage and immature oil palm stage by using the pheromone trap. The data on abundance of Rhinoceros beetle were recorded once every two days for almost a month. Experimental design used in this study was random sampling. The reading comes out with the mean population for the nursery area is higher than immature area. From the total population, the ratio of the population is 60:40 which represent 60% of Rhinoceros beetle recorded in the nursery and the 40% in immature stage area. The result from the study proved that the population of Rhinoceros beetle have tendency to attack more on nursery stage compare to the immature oil palm area. The good sanitation and proper clearing site activity should be carried out to avoid the increasing of population of Rhinoceros beetle.